A feeling for what's best: landscape aesthetics and notions of appropriate residential architecture in Dartmoor National Park, England - Tatum, Kirsten; Porter, Nicole; Hale, Jonathan (Elsevier, 2017)
In England's national parks, the design of new dwellings represents a significant and contested part of landscape planning, inseparable from park conservation ideologies and policies. Within public discourse, new housing proposals can be praised for enhancing the landscape or decried for destroying it, while the decisions of planning authorities legitimise or marginalise different points-of-view. Set in Dartmoor National Park, this paper explores the competing aesthetic interpretations of landscape and the rural as represented within the design and planning of two separate residential sites that were redeveloped between 1998 and 2008. Discourse analysis of interviews (with architects, planners and clients), policies, and written accounts (planning applications and associated correspondence) investigates the positions of various stakeholders in response to these housing projects and to their protected rural landscape settings. Results reveal how notions of landscape context and aesthetics vary across different stakeholder groups, with design quality, sympathetic scale and landscape enhancement proving to be key areas of contention. Differing interpretations of national park planning policy, the problematic nature of communicating and judging qualitative aspects of ‘contemporary’ architecture, and the ongoing emphasis on visual aspects of landscape aesthetics mean that incorporating new housing design within national park landscapes remains challenging.